Navigating Risk And Innovation: Framework For Improving Indonesia's Defense Industry Competitiveness Through Strategic Collaboration - Djansena, Alradix; Aritonang, Sovian (UNIVERSITAS PAKUAN, 2025)
Indonesia's defense industry faces significant challenges, including heavy reliance on foreign technologies and inconsistent implementation of policies like Law No. 16 of 2012, which hampers progress toward self-reliance. This study aims to develop a comprehensive framework integrating innovation and risk management to enhance the competitiveness and independence of Indonesia's defense sector. Using a qualitative research design, the study draws on extensive literature reviews and secondary data analysis, comparing Indonesia's defense industry with that of other countries like South Korea and Turkey. The findings reveal that international and domestic strategic collaborations are essential for technology transfer, improving local capabilities, and aligning defense production with national security goals. Investing in high-performance work systems (HPWS) and human capital fosters technological innovation and reduces foreign dependency. The study also identifies the need for a more consistent regulatory framework and long-term investment in research and development (RD) to address supply chain risks and financial constraints. These insights provide practical recommendations for policymakers, emphasizing that sustainable defense industry growth requires a multifaceted approach involving collaboration between government, industry, and research institutions. Ultimately, this research contributes to the strategic roadmap for achieving Indonesia's defense self-sufficiency and competitiveness in the global market.